The American identity - Allitt, Patrick N.; Teaching Company ([Chantilly, Va.] : The Teaching Company, 2005)
In this course, historian Patrick N. Allitt investigates the American character by introducing notable Americans from all eras of the nation's history, from Thomas Jefferson to Al Capone, whose lives speak on the qualities that make one truly American. The figures in these lectures led fascinating lives, helping one to gain a deeper understanding of the trends and ideas that shaped America and that continue to influence American society today
part 4. lecture 37. Helen Keller-- the inspiration -- lecture 38. Duke Ellington-- the jazzman -- lecture 39. Charles Lindbergh-- the aviator -- lecture 40. Douglas MacArthur-- the world-power warrior -- lecture 41. Leonard Bernstein-- the musical polymath -- lecture 42. Shirley Temple-- the child prodigy -- lecture 43. George Wallace-- the demagogue -- lecture 44. William F. Buckley, Jr.-- the conservative -- lecture 45. Roberto Clemente-- the athlete -- lecture 46. Betty Friedan-- the feminist -- lecture 47. Jesse Jackson-- the civil rights legatee -- lecture 48. Stability and change
Title from title screen
Lecturer: Professor Patrick N. Allitt
Keywords: United States -- History; United States -- Biography